2022
DOI: 10.3390/ijms23052688
|View full text |Cite
|
Sign up to set email alerts
|

CFTR, Cell Junctions and the Cytoskeleton

Abstract: The multi-organ disease cystic fibrosis (CF) is caused by mutations in the gene encoding the CF transmembrane conductance regulator (CFTR) protein, a cAMP regulated chloride (Cl−) and bicarbonate (HCO3−) ion channel expressed at the apical plasma membrane (PM) of epithelial cells. Reduced CFTR protein results in decreased Cl− secretion and excessive sodium reabsorption in epithelial cells, which consequently leads to epithelial dehydration and the accumulation of thick mucus within the affected organs, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…However, scant information is available for the repair of a wounded airway epithelium [ 58 , 59 ]. Given the recognized importance of epithelial junctions in the pathophysiology of CF [ 60 ], this gap should be filled. We have previously shown that hAMSCs and CFBE can form CX43-mediated GJs and that this coupling is involved in the rescue of CFTR function and recovery of other defects presented by CFBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, scant information is available for the repair of a wounded airway epithelium [ 58 , 59 ]. Given the recognized importance of epithelial junctions in the pathophysiology of CF [ 60 ], this gap should be filled. We have previously shown that hAMSCs and CFBE can form CX43-mediated GJs and that this coupling is involved in the rescue of CFTR function and recovery of other defects presented by CFBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its oncogenic potential, YAP1 is tightly regulated by the cytoskeleton, ECM and cell–cell contacts ( 38 ), with a stiff ECM ( 39 ) and lack of cell–cell contacts ( 40 ) both resulting in YAP1 nuclear activity. Disruption of epithelial structures, particularly increased ECM and abnormal cell junctions, are present in the CF lung ( 14 , 41 , 42 ) and likely lead to nuclear YAP1 expression which further potentiates fibrosis and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…A function of CFTR is to transport Cl− and HCO 3− , and it also regulates other ion channels (Na+, K+, Ca 2+ , and other Cl− channels) (20)(21)(22). Additionally, CFTR also has roles in osmoregulation, membrane potential maintenance, lipid homeostasis, cell polarity, the metabolism of glucose and other substrates, oxidative stress, inflammation, mucus production, microbiome alterations, pH regulation, cell motility, autophagy, mitochondrial dysfunction, apoptosis, cell polarity, cell-cell contact, stem cell function, and cellular immune responses (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Some studies have shown multiple associations between CFTR and cancer; however, its expression levels vary between different types of tumors.…”
Section: Discussionmentioning
confidence: 99%